Relative growth and sexual maturity of the stone crab Menippe nodifrons Stimpson, 1859 (Brachyura, Xanthoidea) in southeastern Brazil - Bertini, Giovana [UNESP]; Braga, Adriane Araújo [UNESP]; Fransozo, Adilson [UNESP]; Corrêa, Michéle de Oliveira Dias Alves [UNESP]; Freire, Fulvio Aurélio de Morais [UNESP] (Brazilian Archives of Biology and Technology, 2007)
O objetivo do presente estudo foi determinar o crescimento relativo e a maturidade sexual morfológica de Menippe nodifrons. As coletas foram realizadas na Praia Grande e Tenório, Ubatuba, São Paulo. Os caranguejos foram separados quanto ao sexo e mensurados na região da largura (LC) e comprimento da carapaça, comprimento e altura dos própodos quelares direito e esquerdo, largura do abdome (LA) nas fêmeas e comprimento do gonopódio (CG) nos machos. Obteve-se 399 indivíduos, sendo 195 machos e 204 fêmeas. Os machos atingiram a maturidade sexual com 29,7mm LC e as fêmeas com 31,6mm LC. Para as fêmeas a melhor relação que indicou a muda da puberdade foi LA vs. LC, sendo que o crescimento foi alométrico negativo na fase jovem e alométrico positivo após a muda da puberdade. Para os machos foi CG vs. LC evidenciando crescimento alométrico positivo na fase jovem e isométrico na fase adulta.

The relative growth and size at onset of morphological sexual maturity of the stone crab Menippe nodifrons were investigated. A total of 399 crabs was captured on Praia Grande and Tenório beaches at Ubatuba. Carapace width (CW) and length, cheliped propodus length and height, abdomen width in females, and gonopod length in males were recorded. In females, the abdominal width showed negative allometry for juveniles and positive allometry for adults; the puberty molt occurred at 31.6 mm CW. In males, the size at onset of morphological sexual maturity was estimated as 29.7 mm CW; the gonopod growth showed positive allometry for juveniles, and an isometric relationship for adults. The gonopod length and the abdominal width were the most appropriate morphometric variables to estimate size at onset of sexual maturity in this stone crab.
Keywords: Growth; Sexual Maturity; Menippe; Xanthoidea